2020
DOI: 10.21203/rs.3.rs-37876/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Days away from Work Injury and Associated Factors among Waste Collectors in Mekelle City, Northern Ethiopia: A Cross Sectional Study

Abstract: Background: In its nature, solid waste management is a labour intensive industry, which exposes workers to numerous occupational hazards. This study was aimed to investigate the magnitude of days away from work injuries and associated factors among organized waste collectors in Mekelle city, Northern Ethiopia. Method: A questionnaire and observation checklist based cross-sectional study design was employed from June 1 to 30, 2017. Data was analysed using SPSS for windows 20.0. Descriptive statistics and logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…15,26 Additionally, this study found that the use of personal protective equipment on the job sought to minimize solid waste collectors from suffering occupational injuries that was consistent with studies conducted in India, Egypt, Tanzania, and Ethiopia. 14,15,19,22,26,29…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,26 Additionally, this study found that the use of personal protective equipment on the job sought to minimize solid waste collectors from suffering occupational injuries that was consistent with studies conducted in India, Egypt, Tanzania, and Ethiopia. 14,15,19,22,26,29…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaire was prepared by reviewing previously conducted studies and international organization such as International Labour Organization (ILO). 10 , 14 , 15 , 18 - 23 It was designed to collect information about the prevalence of occupational injuries, socio demographic, behavioral, and other work-related factors. The questionnaire was first prepared in English and translated in to local language (Amharic and Afan Oromo), the local language of study participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation